1995
DOI: 10.1007/bf00051583
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast number in guard cells as ploidy indicator of in vitro-grown androgenic pepper plantlets

Abstract: The number of chloroplasts per guard cell pair and the stomatal length of seventeen anther-derived plants obtained from three pepper donor genotypes were recorded. The haploid plants showed significantly fewer chloroplasts and shorter stomatal length than the diploid plants. Although both characters were positively correlated with the ploidy level, chloroplast number resulted a more reliable method compared to stomatal length to distinguish haploid from diploid in vitro-grown plantlets. The stomatal length val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 9 publications
2
7
1
3
Order By: Relevance
“…Our results were in agreement with previously published reports on other plant species (Beck et al, 2003;Sari et al, 1999;Singsit and Ozias-Akins, 1992;Singsit and Veilleux, 1991). Qin and Rotino (1995) found that chloroplast number in guard cells represented a more reliable and consistent indicator of ploidy in anther-derived pepper plants compared with stomatal cell length and attributed this difference to the fact that chloroplast number is more stable than the size of stomata, which may be more influenced by age and leaf position.…”
Section: Resultssupporting
confidence: 93%
“…Our results were in agreement with previously published reports on other plant species (Beck et al, 2003;Sari et al, 1999;Singsit and Ozias-Akins, 1992;Singsit and Veilleux, 1991). Qin and Rotino (1995) found that chloroplast number in guard cells represented a more reliable and consistent indicator of ploidy in anther-derived pepper plants compared with stomatal cell length and attributed this difference to the fact that chloroplast number is more stable than the size of stomata, which may be more influenced by age and leaf position.…”
Section: Resultssupporting
confidence: 93%
“…The ploidy level was also estimated by the number of chloroplasts in the guard cells i.e. Similar to this study, the chloroplast index of stomatal guard cells have been successfully used for the assessment of haploid plants in pepper [19,20]. 1j); whereas their number was 14-15 in the guard cells of the stomata of donor plants (Fig.…”
Section: Ploidy Level Of Regenerated Plantssupporting
confidence: 57%
“…Ploidy level can be more easily assessed by flow cytometry analysis (Bohanec 2003). Ploidy level can also be estimated by indirect methods, such as those based on chloroplast counts in stomatal guard cells and plastid dimensions (Lee and Hecht 1975;Qin and Rotino 1995;Yuan et al 2009). …”
Section: Characterization Of Regenerants: Ploidy Analysismentioning
confidence: 99%